PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT TERHADAP HASIL BELAR IPA SISWA SD NEGERI 15 INDERALAYA UTARA - Anglusia, Nopriyani (SCHOLASTICA JOURNAL : JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2018)
ABSTRACTThe purpose of this reseach to know the effect of cooperative learning model type team games tournament to see learning outcomes Science of primary school 15 Inderalaya Utara. The population is all of students in Primary School 15 Indralaya Utara. The sample is five grade with 34students as experimen class and 34 students as compare class. Methods of this reseach is experimen semu. Data collection used test tehniques with writting test. The writting test question analysed used validitas, reliabilitas and difficulties level test. The result tests analyzed with uji homogenitas, uji normalitas and uji-t. Based of analyzed, experiment class and compare class was homogen, distribution normal and  that means there are different average learning outcomes from experiment and compare class. Can be concluded there is effect from implemation cooperative learning type team games tournament to ipa learning outcome in primary school 15 Indralaya Utara. Keywords: learning models, TGT, learning outcomes.